Konseling Online Sebagai Salah Satu Bentuk Pelayanan E-konseling - Ifdil Ifdil; Zadrian Ardi (Jurnal Konseling dan Pendidikan, 2013)
The development of technology has changed the lives of the world as well as counseling. Counseling is not only face to face (FTF) in a confined space, but it can be done through distance format in assistive technology that online counseling. Counseling is an integral part of e-counseling services. Various applications have been developed to support the implementation of BK in Indonesia, as well as with use of other technologies that can support the implementation of guidance and counseling services. E-counseling services in general and in particular online counseling are an alternative attempt to do by counselors in an effort to prevent, reduce and eliminate the problem. Counselors should have a mastery of the technology and has a minimum competency in the administration of e-counseling services, at least insights about e-counseling services. This article will present a variety of things with regard to e-counseling service specifically about online counseling